2000
DOI: 10.1111/1467-9914.00146
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation and Employment Reallocation

Abstract: International audienceThe paper describes the dynamics of employment at a firm and sector level in the French industry and examines how far technological innovation can give account of it. We use a firm sample of 15,186 firms, over the 1986-1990 period. The two facts we want to explain at a firm level and a sector level are the net change in employment and the micro turmoil (transfers between competing firms). Innovating firms and sectors create jobs more than others over medium run (5 years). Process innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
0
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 11 publications
(16 reference statements)
15
101
0
6
Order By: Relevance
“…This shows that the heterogeneity regarding employment decisions that we observe for the manufacturing industry, is still apparent even after disaggregating at narrowly defined industries. The same result has been found for some other countries (see Davis and Haltiwanger (1992), Konings (1995) and Greenan and Guellec (1997) among others). Job creation ranges from 0.8 percent in iron steel and metal to 6.8 percent in plastic materials; job destruction from 4.0 percent in other non-basic industries to 7.3 percent in food, tobacco and drinks; and job reallocation varies from 5.3 percent in iron steel and metal to 13.0 percent in office machinery.…”
Section: Figure 1 : Employment Growth Histogramsupporting
confidence: 88%
See 1 more Smart Citation
“…This shows that the heterogeneity regarding employment decisions that we observe for the manufacturing industry, is still apparent even after disaggregating at narrowly defined industries. The same result has been found for some other countries (see Davis and Haltiwanger (1992), Konings (1995) and Greenan and Guellec (1997) among others). Job creation ranges from 0.8 percent in iron steel and metal to 6.8 percent in plastic materials; job destruction from 4.0 percent in other non-basic industries to 7.3 percent in food, tobacco and drinks; and job reallocation varies from 5.3 percent in iron steel and metal to 13.0 percent in office machinery.…”
Section: Figure 1 : Employment Growth Histogramsupporting
confidence: 88%
“…The contributions in this line for other countries are numerous. We can mention, among others, Konings (1995) and Blanchflower and Burgess (1996) for the UK, Greenan and Guellec (1997) for France, and Dolado and Gómez (1995), Díaz-Moreno and Galdón-Sánchez (2000), and Ruano (2000) for Spain. Although all these contributions exploit longitudinal data, they differ notably in the level of data disaggregation, in the length of the sample period, and in the data coverage.…”
Section: Introductionmentioning
confidence: 98%
“…These authors find that although process innovation displaces employment, compensation effects from product innovation seem to dominate, albeit with some differences across countries. 2 Greenan and Guellec (2000), also combining firm-level panel data with innovation surveys, find that innovating firms (and industries) have created more jobs than non-innovating ones. Piva and Vivarelli (2005), combining different surveys by Mediocredito-Capitalia from 1992-1997, build a balanced panel of 575 Italian Manufacturing firms and find a small but significant positive relation between innovative investments and employment.…”
Section: Theoretical and Empirical Underpinningsmentioning
confidence: 99%
“…These authors found for some European countries in the late 1990s job losses in the manufacturing industry due to technological change; because of an active price competitiveness strategy, technological efforts were associated to restructuring and the market expansion effect of new products was modest. Greenan and Guellec (2000) states that for France, at the firm level, process innovation creates more jobs than product innovation while the opposite occurs at the sectoral level. However, innovative firms perform better than the others on the medium-run.…”
Section: Between 65% and 75% Of Total I And D Activities In Countries Lmentioning
confidence: 99%